Color Doppler ultrasound versus CT angiography for DIEP flap planning: A randomized controlled trial - Bajus, Adam; Streit, Libor; Kubek, Tomáš; Novák, Adam; Vaníček, Jiří; Šedivý, Ondřej; Berkeš, Andrej; Bayezid, K Can; Kunovský, Lukáš; Dražan, Luboš (Journal of plastic, reconstructive & aesthetic surgery, 2023)
BACKGROUND: Identifying relevant perforators is crucial in planning a deep inferior epigastric perforator (DIEP) flap. Color Doppler ultrasonography (CDU) has gained popularity for localizing perforators; however, current evidence on its efficiency is still inconclusive. This study aimed to compare the efficiency of CDU with that of computed tomography angiography (CTA) in localizing and selecting the relevant perforators. METHODS: In this randomized controlled trial, 60 patients undergoing DIEP flap breast reconstruction (uni- or bilateral) were randomly assigned to the CDU group (i.e., CDU was performed to map and select the relevant perforators preoperatively) or the CTA+CDU group (i.e., mapping was based on CTA and supplemented by CDU). CDU was performed by the same surgeon with a well-defined sonography experience from our previous study. The reference XY coordinates of the dissected perforators were measured intraoperatively, and deviations from preoperatively deducted coordinates were calculated (ΔCDU or ΔCTA+CDU). The flaps were categorized according to the number of dissected perforators, and adherence to the preoperative strategy was evaluated. RESULTS: Overall, 22 patients (30 flaps) in the CTA+CDU group and 27 (39 flaps) patients in the CDU group were evaluated. The average ΔCDU (0.6 cm) was significantly lower than the average ΔCTA+CDU (1.0 cm) (p < 0.001). Adherence to the mapping-based dissection strategy was higher in the CDU group; however, the difference was insignificant (p = 0.092). CONCLUSION: CDU is not inferior to CTA + CDU in localizing and selecting relevant DIEA perforators. Therefore, CDU mapping is a possible complementary or substitute modality for CTA mapping.
Keywords: mamoplastika; DIEP flap perforator mapping; perforátorový lalok; Computed tomographic angiography; Humans; Perforator Flap; Epigastric Arteries; Breast reconstruction; Localization of perforators; CT angiografie; lidé; Ultrasonography, Doppler, Color; Color Doppler ultrasound; Perforator flaps; Computed Tomography Angiography; arteriae epigastricae; ultrasonografie dopplerovská barevná; Mammaplasty